Cyber Terrorism Challenges : The Need for a global Mutual Legal Assistance to a Universal Jurisdiction Crime - Yasniar Rachmawati Madjid (Faculty of Law, Universitas Sebelas Maret, 2021)
Terrorism is a crime which involved more than one state to attack world peace and security. The handling of international terrorism is not only based on national law but also on international law. With the widespread concerns about cyber terrorism and the frequent use of the term “cyber terrorism“ at the present time, many international organization have made efforts to combat this threat. Since cyber terrorism is an international crime, local regulations alone are not able to defend against such attacks, they require Mutual Legal Assistance between States and a transnational response. Therefore, an attacked country will invoke international law to seek justice for any damage caused, through the exercise of universal jurisdiction. Cyber terrorism can’t be prevent just only with national regulation, the need for and international corporation between states to prevent and defend nations from cyber terrorism attacks. This article discusses about cyber terrorism is a transnational/international crime, it should be subjected to universal jurisdiction trough multinational corporation, and this would be the most suitable method to counter future transnational crime such as cyber terrorism.